Structural Fire Engineering: Overview and Application Examples of Appendix 4 of the AISC Specification - Gross, John; Iwankiw, Nestor; Johann, Matthew (Engineering Journal, 2013)
This paper presents an overview of current conventional practices for providing passive fire protection of building structures and describes alternative engineering approaches covered in Appendix 4 of the 2010 AISC Specification, ANSI/AISC 360-10. The concept of structural fire engineering is discussed, along with guidance and design references that are available to support performance-based structural fire engineering analyses. The roles and responsibilities typically assumed by design team members and other stakeholders in a structural fire engineering project are presented, as are considerations associated with peer reviews and approval by authorities having jurisdiction. The paper concludes with a series of four design examples that demonstrate a range of structural fire engineering applications for steel buildings.